The effectiveness of store brand products towards customers at Carrefour Sri Petaling in year 2008 / Emylia Mohd Khairuddin - Mohd Khairuddin, Emylia (Faculty of Business and Management, 2008)
Store brands have an important role in retail strategy due to their increasingly important strategic role for retailers. Therefore, understanding the store brand buyer behavior is a critical issue for marketers and researchers alike. Intensive competition, fast technological innovation is the retail industry has had a considerable impact on the management of the retail industry in developing and executing new competitive marketing strategies. One of the most commonly implemented marketing strategies of retailers has been the introduction of their own retail (private label or store) brands. "Store brands" or "private ;Iabel" refer to merchandise that carry wholesaler's or retailer's own brand name or a brand name created exclusively for that particular wholesaler or retailer. In this study, store brand products are defined as the "... products owned and branded by the organizations whose primary objective is distribution rather than production (Schutte 1969).